TrpC3 regulates hypertrophy-associated gene expression without affecting myocyte beating or cell size. - Jacob S Brenner; Ricardo E Dolmetsch (PLoS ONE)
Pathological cardiac hypertrophy is associated with an increased risk of heart failure and cardiovascular mortality. Calcium (Ca(2+)) -regulated gene expression is essential for the induction of hypertrophy, but it is not known how myocytes distinguish between the Ca(2+) signals that regulate contraction and those that lead to cardiac hypertrophy. We used in vitro neonatal rat ventricular myocytes to perform an RNA interference (RNAi) screen for ion channels that mediate Ca(2+)-dependent gene expression in response to hypertrophic stimuli. We identified several ion channels that are linked to hypertrophic gene expression, including transient receptor potential C3 (TrpC3). RNAi-mediated knockdown of TrpC3 decreases expression of hypertrophy-associated genes such as the A- and B-type natriuretic peptides (ANP and BNP) in response to numerous hypertrophic stimuli, while TrpC3 overexpression increases BNP expression. Furthermore, stimuli that induce hypertrophy dramatically increase TrpC3 mRNA levels. Importantly, whereas TrpC3-knockdown strongly reduces gene expression associated with hypertrophy, it has a negligible effect on cell size and on myocyte beating. These results suggest that Ca(2+) influx through TrpC3 channels increases transcription of genes associated with hypertrophy but does not regulate the signaling pathways that control cell size or contraction. Thus TrpC3 may represent an important therapeutic target for the treatment of cardiac hypertrophy and heart failure.